2004
DOI: 10.1046/j.1529-8817.2004.03034.x
|View full text |Cite
|
Sign up to set email alerts
|

NITROGENOUS NUTRITION OF ALEXANDRIUM CATENELLA (DINOPHYCEAE) IN CULTURES AND IN THAU LAGOON, SOUTHERN FRANCE1

Abstract: Alexandrium catenella (Whedon et Kofoid) Balech was isolated from Thau lagoon (northern Mediterranean) and its growth and uptake characteristics measured for nitrate, ammonium, and urea. Although affinity constants did not indicate a preference for ammonium over nitrate, there was a strong inhibition of nitrate uptake by ammonium when both nitrogen (N) sources were present. Nitrogen budgets during growth in cultures revealed major imbalances between decreases in dissolved N and increases in particulate N, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
3
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 33 publications
5
91
3
3
Order By: Relevance
“…On the other hand, the biomass of cyanobacteria and chrysophytes was higher in the daily than in the weekly enrichments. The results are only partly in accordance with the results of Sommer (1985), who in a laboratory experiment with freshwater algae found that a pulsed P addition contributed to the advantage of chlorophytes but also to a storage specialist Aphanizomenon flos-aquae (cyanobacteria).The reason that storage specialists, like large dinoflagellates (Dortch et al 1984, Collos et al 2004) and cyanobacteria (Larsson et al 2001, Walve 2002, were not favored by the pulsed nutrient supply in the present study may be that the ability of phytoplankton to store N depends on the type of nitrogen source (Stolte et al 1994, Stolte & Riegman 1996. NH 4 + , which was used in this experiment, is a positive-charged or neutral (NH 3 ) molecule that may not be a suitable storage product, because it can easily diffuse across biological membranes (Stolte et al 1994).…”
supporting
confidence: 81%
“…On the other hand, the biomass of cyanobacteria and chrysophytes was higher in the daily than in the weekly enrichments. The results are only partly in accordance with the results of Sommer (1985), who in a laboratory experiment with freshwater algae found that a pulsed P addition contributed to the advantage of chlorophytes but also to a storage specialist Aphanizomenon flos-aquae (cyanobacteria).The reason that storage specialists, like large dinoflagellates (Dortch et al 1984, Collos et al 2004) and cyanobacteria (Larsson et al 2001, Walve 2002, were not favored by the pulsed nutrient supply in the present study may be that the ability of phytoplankton to store N depends on the type of nitrogen source (Stolte et al 1994, Stolte & Riegman 1996. NH 4 + , which was used in this experiment, is a positive-charged or neutral (NH 3 ) molecule that may not be a suitable storage product, because it can easily diffuse across biological membranes (Stolte et al 1994).…”
supporting
confidence: 81%
“…According to Harrison (1976), Nedwell et al (2002) and Badylak & Philips (2004), these conditions may favor the growth and proliferation of dinoflagellates species. Collos et al (2004) and Imai et al (2006) showed also that deficiency of phosphorus in coastal areas can favor the development of some toxic dinoflagellates, such as the Alexandrium genus.…”
Section: Discussionmentioning
confidence: 99%
“…Urea uptake rates in aquatic systems range from < 0.1 nM-N h -1 to 3.6 µM-N h -1 (Kristiansen 1983, Berg et al 1997, Lomas et al 2002, Berman & Bronk 2003. Sometimes, rates of urea uptake can meet most of the phytoplankton demand for N. For example, urea has been observed to support a large fraction of the N demand of many HABs including the dinoflagellate Lingulodinium polyedrum off the coast of Mexico (Kudela & Cochlan 2000), the dinoflagellate Alexandrium catenella in Thau Lagoon in Southern France (Collos et al 2004), and the pelagophyte Aureococcus anophagefferens in Great South Bay and Peconic Bay, New York (Lomas et al 1996, Berg et al 1997, Gobler et al 2002.…”
Section: Rates Of Urea Uptakementioning
confidence: 99%
“…The recent availability of genome sequences from several types of phytoplankton has offered a great deal of insight into the role of urea in phytoplankton metabolism. One phytoplankton taxon that plays an important part in urea utilization in marine ecosystems, but has not had a genome completely sequenced yet, is the dinoflagellates (Kudela & Cochlan 2000, Collos et al 2004, Jauzein et al 2008a Leftley & Syrett 1973, Bekheet & Syrett 1977. The standard biochemical assay for urease detects high activity in dinoflagellates (Figs.…”
Section: Phytoplankton Genome Sequencesmentioning
confidence: 99%